126 Advanced Assessment of Cardiac Morphology and Prediction of Gene Carriage by CMR in Hypertrophic Cardiomyopathy - The HCMNET/UCL Collaboration. (31st May 2014) - Captur, Gaby; Mohun, Timothy J; Finocchiaro, Gherardo; Wilson, Robert; Levine, Jonathan; Conner, Lauren; Lopes, Luis; Patel, Vimal; Sado, Daniel M; Li, Chunming; Bassett, Paul; Herrey, Anna; et al.
Abstract : Introduction: Myocardial abnormalities have been identified in hypertrophic cardiomyopathy(HCM) gene mutation carriers without hypertrophy(G+LVH-). Some of these changes may be mutation-related but whether they can predict gene carriage in relatives of HCM probands is unknown. We developed a method for tracking trabecular and mitral valve(MV) development in embryonic mouse hearts using high-resolution episcopic microscopy(HREM). We used these insights to instruct on human cardiac morphology by cardiovascular magnetic resonance(CMR) hypothesising that a combination of cardiac abnormalities could predict gene carriage in HCM before the appearance of LVH. Method: MOUSE DEVELOPMENT-63 Wild-type hearts were examined from the time of ventricular septation till just before birth. Trabeculae ware charted by box-counting fractal analysis. MV volumes were calculated from 3D volumetric reconstructions of HREM datasets. HUMAN MORPHOLOGY-74 G+LVH- sarcomere mutation carriers (29 ± 13 yr [SD] 51% M) were identified in 12 US-centres(HCMNet n35) and UCL (n39). Subjects underwent CMR and fractal analysis. Results were compared with 111 overt HCM patients(G+LVH+ n71;G-LVH+ n40) and 136 matched controls(36 ± 16 yr 63% M). We analysed a single-centre (UCL) G+LVH- case-control cohort to identify factors associated with gene carriage evaluating anterior MV leaflets (AMVL), wall thickness, clefts, trabeculae and other variables. We validated associations in the multicenter HCMNet and combined parameters into a model predicting gene carriage. Results: In developing mice MV volumes trebled between stages E14.5 to 18.5 and a fractal atlas tracked trabecular development revealing a basal drop in LV trabecular complexity(E14.5–18.5 p < 0.0001 Figure 1 ). Contrasting the UCL case-control populations 5 differences were borne out in the validation cohort (Figure 2 ). These were: I) longer AMVL(22 ± 3 vs 20 ± 3 mm p < 0.0001); II) increased maximal-apical trabecular complexity(1.242 ± 0.07 vs 1.196 ± 0.05 p < 0.0001); III) increased maximal-septal systolic wall thickness(13 ± 3 vs 12 ± 2 mm p = 0.02); IV) lower indexed-end-systolic LV volume(23 ± 6 vs 26 ± 7 mls/m 2 p = 0.005); and V) presence of clefts(35 vs 7% p < 0.0001). Conditional logistic regression provided a model containing these parameters which predicted gene carriage with a high level of accuracy (78%). Conclusion: The normal pattern of cardiac trabecular and MV development may be studied in mouse using HREM. Similar approaches applied to CMR in humans reveal cardiac structural abnormalities in HCM gene mutation carriers even in the absence of LVH. These abnormalities are an early phenotype of sarcomere mutations and a CMR imaging pentad exhibits promising potential for predicting gene carriage in HCM.